Lurasidone: an antipsychotic with antidepressant effects in bipolar depression?. (June 2016) - Keks, Nicholas A; Hope, Judy; Castle, David
Objective: Lurasidone is a new serotonin–dopamine antagonist atypical antipsychotic which also appears to be effective in bipolar depression. This paper will briefly review the evidence concerning lurasidone. Conclusions: Lurasidone is an antagonist at dopamine D2, serotonin 5-HT2 and 5-HT7, and partial agonist at 5HT1a receptors; it has no anticholinergic or antihistaminic activity. Rapidly absorbed, it has a half-life of 18 ± 7 hours, will reach steady state in five days and is taken at night with food (absorption is halved on an empty stomach). It is hepatically metabolised with some potential for interactions. Lurasidone is an effective antipsychotic in acute schizophrenia, and non-inferior to quetiapine but not risperidone in 12-month studies. Lurasidone may cause mild sedation, nausea, agitation, insomnia and akathisia (especially at initiation). Risks for weight gain, hyperprolactinaemia and QTc prolongation are low. Lurasidone has demonstrated antidepressant efficacy both as monotherapy and in addition to lithium or valproate in bipolar depression, of a comparable degree to that seen with the combination of olanzapine and fluoxetine. Lurasidone appears to be a "metabolically-friendly" antipsychotic for schizophrenia where weight gain and hyperprolactinaemia are of concern, and may also prove useful in bipolar depression (although not approved for this condition in Australia).